Penguatan Kecerdasan Ayat Qauliyah, Kauniyah Dan Insaniyah (Pendekatan Metakosmos, Makrokosmos dan Mikrokosmos) - Riviana, Natta; M, Amril; Dewi, Eva (Indonesian Journal of Islamic Educational Management, 2025)
This study aims to analyze the enhancement of human intelligence through three types of verses in the Qur’an: qauliyah (scriptural), kauniyah (cosmic), and insaniyah (human-related), using the Metacosmos, Macrocosmos, and Microcosmos theory. The research employs a qualitative method with literature analysis as the primary instrument. The research subject is the concept of intelligence from the Qur’anic perspective, while the objects include qauliyah, kauniyah, and insaniyah verses. Data collection was conducted through literature review, and data analysis applied a hermeneutic approach to interpret the verses. The findings indicate that a profound understanding of these three types of verses can enhance spiritual, intellectual, and emotional intelligence while strengthening human relationships with themselves, nature, and the Creator. The study concludes that integrating qauliyah, kauniyah, and insaniyah verses within the Metacosmos, Macrocosmos, and Microcosmos framework can serve as a foundation for holistic intelligence development.